Geomorphological features, Permanent Preservation Areas and implantation of megaproject of urban/hotel infrastructure in the Via Costeira of Natal/RN - Melo, Marceu; Cestaro, Luiz Antonio; Galvão, Frederico Fonseca (Sociedade & Natureza, 2018)
The planet's coastline supports several economic activities, shelters a large part of the world's population and is considered an environment of relative fragility. The development of touristic activity in theRio Grande do Norte is directly associated to the coast and acquired greater relevance in the late 1970sand early 1980s, in the context of a policy of touristic megaprojects, through the implementation of theVia Costeira project, which aimed to enlarge the hotel capacity of Natal, the capital of Rio Grande doNorte. The project generated a lot of controversy, was criticized and reformulated due to the naturalcharacteristics of the area proposed for its installation, mostly covered by non-vegetated dunes and somestretches covered by Rain Forest, but it was approved. The objective of this study was to verify whichgeomorphological elements were affected for its implementation and, from these, to delimit the PermanentPreservation Areas (APP) defined by the legislation. The results showed that the project was carried outalmost entirely on APP. We conclude that the most appropriate measure is to declare unoccupied stretchesas non-aedificandi areas and to carry out recovery projects for degraded areas.